Whatever Happened to the Black Swedes? Ola Larsmo’s Maroonberget - Brantly, Susan (Journal of Northern Studies, 2008)
This article examines how historical fiction can impact a nation’s narrative of itself, and hence, issues of national identity. Ola Larsmo’s Maroonberget (1996) presents a story that challenges the narrative of Swedish homogeneity by tracing a history of black Swedes back to the 1700s. The novel undermines binary oppositions such as white/black and Swede/Immigrant by positing a model of hybridity. The reception of the novel in the Swedish press is examined in order to gauge the reactions to Larsmo’s novel in the contemporary cultural debate.